Segmental motor recovery after cervical spinal cord injury relates to density and integrity of corticospinal tract projections - Balbinot, Gustavo; Li, Guijin; Kalsi-Ryan, Sukhvinder; Abel, Rainer; Maier, Doris; Kalke, Yorck-Bernhard; Weidner, Norbert; Rupp, Rüdiger; Schubert, Martin; Curt, Armin; Zariffa, Jose (Nature Communications, 2023)
Cervical spinal cord injury (SCI) causes extensive impairments for individuals which may include dextrous hand function. Although prior work has focused on the recovery at the person-level, the factors determining the recovery of individual muscles are poorly understood. Here, we investigate the muscle-specific recovery after cervical spinal cord injury in a retrospective analysis of 748 individuals from the European Multicenter Study about Spinal Cord Injury (NCT01571531). We show associations between corticospinal tract (CST) sparing and upper extremity recovery in SCI, which improves the prediction of hand muscle strength recovery. Our findings suggest that assessment strategies for muscle-specific motor recovery in acute spinal cord injury are improved by accounting for CST sparing, and complement person-level predictions.